Debt Management Performance Assessment Methodology - World Bank Group (World Bank, Washington, DC, 2015)
The World Bank has developed a program, in collaboration with other partners, to assist developing countries in improving debt management. The objective of the program is to help strengthen capacity and institutions in developing countries so that they can manage government debt in an effective and sustainable manner in the medium to long term. A cornerstone of the program is the debt management performance assessment (DeMPA) tool, a methodology for assessing performance through a comprehensive set of performance indicators spanning the full range of government DeM functions. The DeMPA highlights strengths and weaknesses in government DeM practices in each country. Performance assessment facilitates the design of plans to build and augment capacity and institutions in ways tailored to country-specific needs. The DeMPA also facilitates the monitoring of progress over time in achieving government DeM objectives in a manner consistent with international sound practice. This document provides additional background and supporting information so that a non-specialist in DeM may undertake a country assessment effectively.